2011
DOI: 10.1055/s-0031-1300454
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Mechanism of Lafutidine, a Novel Anti-ulcer Drug with Histamine H2-Receptor Antagonistic Activity

Abstract: Lafutidine (CAS 118288-08-7, FRG-8813) is a novel histamine H2-receptor antagonist with gastroprotective activity. The aim of this study was to investigate the property of the gastro-protective activity of lafutidine by examining the effect on ammonia-induced change in transmucosal potential difference (PD), basal gastric mucosal blood flow (GMBF) and noxious agent-induced cell damage. Intragastrical application of lafutidine accelerated the recovery of the PD reduction after exposure of the mucosa to 0.25% am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Even the new drug "Lafutidine" a Histamin-2-receptor (H 2 R) blocking compound, that was developed in the medical treatment of GI mucosal damage and marketed in Japan (Ajioka et al 2000(Ajioka et al , 2002Onodera et al 1999;Takeuchi 2006) showed typical capsaicin actions at the target organ.…”
Section: Introductionmentioning
confidence: 99%
“…Even the new drug "Lafutidine" a Histamin-2-receptor (H 2 R) blocking compound, that was developed in the medical treatment of GI mucosal damage and marketed in Japan (Ajioka et al 2000(Ajioka et al , 2002Onodera et al 1999;Takeuchi 2006) showed typical capsaicin actions at the target organ.…”
Section: Introductionmentioning
confidence: 99%
“…[2] It is absorbed in the small intestine, reaches gastric cells via the systemic circulation, and rapidly binds to gastric cell histamine H2 receptors, resulting in immediate inhibition of gastric acid secretion. [3] Lafutidine has been shown to increase the gastric mucosal blood flow [4] and gastric mucus secretion [5,6] also accelerate sepithelial restitution in rats. Lafutidine has a receptor binding affinity, which is 2-80 times higher than famotidine, ranitidine and cimetidine.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study demonstrated that lafutidine does not influence the impaired healing of epithelial wounds in RGM1 cells under in vitro conditions without neuronal innervations (Murashima et al, 2009), again confirming the importance of sensory neurons in the healing-promoting action of this agent. Several studies show that luminal lafutidine stimulates capsaicin-sensitive afferent nerves via presumably direct diffusion rather than after its absorption from intestine followed by via circulation, suggesting the rapid local diffusion reaching to the afferents before H 2 -receptor blockade from the circulation (Onodera et al, 1999b;Nagahama et al, 2003). Second-generation H 2 -receptor antagonists such as lafutidine are thought to facilitate capsaicin-sensitive sensory afferent nerves and exert gastroprotective effects through CGRP and in part via NO release in the stomach.…”
Section: Mechanisms Of Gastroprotective Actionsmentioning
confidence: 99%